Information, misinformation, disinformation, and anti-vaccine movements: Materiality of enunciations in information regimes - Vignoli, Richele Grenge [UNESP]; Rabello, Rodrigo [UNESP]; De Almeida, Carlos Cândido [UNESP] (My University, 2021)
Objetive: This essay aims to ponder information, misinformation and disinformation as a means used by Anti-vaccine movements, addressing the production of their social effects in terms of materiality and institutionality of enunciations within information regimes Methods: Bibliographic review focused on materiality and institutionality of enunciations, information, disinformation, information regimes, and anti-vaccine movements. Furthermore, consulting Brazilian governmental websites and legislation made reflections on the topics of this study viable. Results: The reflections point toward the materiality of misinformation and disinformation as a source or product of anti-vaccine discourses, which, at times, mimics resorts employed in public State policies, in a context in which previously eradicated immunopreventable diseases reappear, such as the case of measles in Brazil. Conclusions: The difficulty in distinguishing information from misinformation and disinformation constitutes a problem for the State, for Science, for public health entities, or for means of communication, and institutions of mediation, committed to information. The capitalized confirmation bias from anti-vaccine movements stands out as a means of resistance and/or confrontation to the control of the State. Vaccinations’ side effects can be used out of context to reinforce the idea that “every vaccine is harmful.” Science and the public power face the challenge of clarifying public opinion on the benefits and care to be taken concerning vaccines.
Informação, misinformação, desinformação e movimentos antivacina: Materialidade de enunciados em regimes de informação
Keywords: Anti-vaccine movements; Disinformation; Enunciations; Information; Information regimes; Materiality; Misinformation